Application of the Principle of Consensuality and its Legal Implications In Electronic Contracts at Shopee - SUTIYOSO, Bambang; PARMITASARI, Indah (International Journal of Environmental, Sustainability, and Social Science, 2023)
Abstract This study aims to examine and analyze the application of the principle of consensuality in electronic contracts at Shopee: and how the legal implications of the application of the principle of consensuality in electronic contracts at Shopee. The research method used is normative juridical with a statutory and conceptual approach, using secondary legal data and analyzed with a qualitative descriptive method. The results showed that in electronic contracts at Shopee, the principle of consensualism has been applied. In this case, the electronic contract is carried out by means of a click-wrap agreement, namely to determine the agreement in the e-contract is when the party receiving the offer "clicks" on the agreement section. E-contract in Shopee can be said to be an agreement between computer users (users) in interacting with producers or electronic service providers. The application of the principle of consensuality in electronic contracts at Shopee, raises several legal implications, namely: 1) the existence of consensualism gives birth to an electronic contract; 2) the enactment of the principle of Pacta Sun Servanda, meaning that the agreed electronic contract is fully binding and therefore must be obeyed; 3) and for the transfer of rights, consensualism must be followed by a material contract (zakelijke overeenkomst), with the concrete form of this material contract being the act of delivery (levering) of the object in question from the seller's hands to the buyer's hands. Keywords: Application, Consensuality Principle, Electronic Contract, Shope